Magnetic Temperature-Sensitive Solid-Lipid Particles for Targeting and Killing Tumor Cells - Świętek, Małgorzata; Panchuk, Rostyslav; Skorokhyd, Nadia; Černoch, Peter; Finiuk, Nataliya; Klyuchivska, Olha; Hrubý, Martin; Molčan, Matúš; Berger, Walter; Trousil, Jirí; Stoika, Rostyslav; Horák, Daniel (Frontiers in Chemistry, 2020)
Magnetic and temperature-sensitive solid lipid particles (mag.SLPs) were prepared in presence of oleic acid-coated iron oxide (IO-OA) nanoparticles with 1-tetradecanol and poly(ethylene oxide)-block-poly(ε-caprolactone) as lipid and stabilizing surfactant-like agents, respectively. The particles, typically 850 nm in hydrodynamic size, showed heat dissipation under applied alternating magnetic field. Cytotoxic activity of mag.SLPs, nonmagnetic SLPs, and iron oxide nanoparticles was compared concerning mammalian cancer cell lines and their drug-resistant counterparts using trypan blue exclusion test and MTT assay. The mag.SLPs exhibited dose-dependent cytotoxicity against human leukemia cell lines growing in suspension (Jurkat and HL 60/wt), as well as the doxorubicin- and vincristine-resistant HL-60 sublines. The mag.SLPs showed higher cytotoxicity towards drug-resistant sublines as compared to Dox. The human glioblastoma cell line U251 growing in a monolayer culture was also sensitive to mag.SLPs cytotoxicity. Staining of U251 cells with fluorescent dyes Hoechst 33342 and propidium iodide (PI) revealed that mag.SLPs treatment resulted in increased number of cells with condensed chromatin and/or fragmented nuclei as well as with blebbing of plasma membranes. While the Hoechst 33342 staining of cell suggested the pro-apoptotic activity of particles, the PI staining indicated the pro-necrotic changes in the target cells. These conclusions were confirmed by Western blot analysis of apoptosis-related proteins, study of DNA fragmentation (DNA laddering due to the inter-nucleosomal cleavage and DNA comets due to single strand breaks), as well as by FACS analysis of the patterns of cell cycle distribution (pre-G1 phase) and Annexin V/PI staining of the treated Jurkat cells. The induction of apoptosis or necrosis by the particles used to treat Jurkat cells depended on the dose of the particles. The induction of apoptosis or necrosis in Jurkat cells depended on the particle dose. Production of the reactive oxygen species (ROS) was proposed as a potential mechanism of mag.SLPs-induced cytotoxicity. Accordingly, hydrogen peroxide and superoxide radical levels in mag.SLPs-treated Jurkat leukemic cells were increased by 20-40 % and 70 %, respectively. In contrast, the nonmagnetic SLPs and neat iron oxides did not influence ROS levels significantly. Thus, the developed mag.SLPs can be used for effective killing of human tumor cells, including drug-resistant ones.